Evaluación del efecto de abono orgánico a base de estiércol de ovino en el cultivo de dos híbridos de brócoli ( Brassica oleracea L.) en la Granja Experimental PUCE -SI - Regalado Mafla, Johan Paul (2023)
The dose to be applied to the soils of organic amendments for the improvement of soil fertility based on the use of sheep manure, especially for the cultivation of vegetables, allows guiding the adequate use of available resources. The present investigation studied the behavior of organic amendments applied in a high dose at a rate of 10 kg/m², a medium dose of 8 kg/m² and a low dose of 6 kg/m²\; Complementing the missing elements with a complete mineral fertilizer with a ratio of 1N-1P2O5-1K2O (15-15-15) at a rate of 20 g per m². The research was carried out under the agroecological conditions of the experimental farm of the Pontificia Universidad Católica del Ecuador, Ibarra campus. Two hybrid Broccoli materials (Avenger and Zafiro) were used. For the development of the trial, a randomized complete block design (DBCA) was used in a divided plot arrangement. The variables evaluated were: the height of the broccoli plants at 30, 60 and 90 days\; the diameter of the stem at 30, 60 and 90 days, the diameter of the pellet\; pellet weight and yield. In determining the changes in the morphophysiological behavior of the broccoli plant, it was observed that the amendment of organic fertilizer of medium sheep manure (8 kg of manure) with the hybrid of Zafiro broccoli presented the highest yield of 0.54 kg/m² under open field conditions with a benefit cost per ha of 1.96. Accepting the null hypothesis where the treatments are similar, reaching the conclusion that the amendments and fertilization based on a mineral formula of complete fertilizer 15-15- 15, NPK are the same in the morphological changes of the broccoli plant for height of plant, pellet diameter and pellet weight.